UPAYA PENGEMBANGAN UMKM PADA OBJEK WISATA SENDANG MBEJI DI DESA KEMIRI BERBASIS EKONOMI KREATIF - Tri Nurdyastuti; Suroto Suroto; Mulyadi Mulyadi; Rina Ani Sapariyah; Dibyo Iskandar (Sekolah Tinggi Ilmu Ekonomi AMA, 2023)
MSMEs around Sendang Mbeji have problems with human resources, capital, and mastery of modern technology. The community service team is trying to provide solutions with the theme of efforts to develop creative economy-based MSMEs. Creative economy is a concept in the field of economics in the new economic era by prioritizing creativity and information. The devotion-based research implementation method is carried out in three stages, namely lectures, mentoring and problem solving. The results of the dedication shown show success in developing creative economy-based MSMEs in the practice of creating their products, as well as improving the income of MSME actors. The results of the dedication can also provide education about the use of technology in online promotions.